Pengujian Sistem Informasi Kontrol Stok Barang Pendukung Produksi Berbasis Web Dengan Metode User Acceptance Testing (UAT) Pada PT. Tenma Cikarang Indonesia - Isarianto; Rina Patmawati (Prosiding Sains dan Teknologi, 2024)
An information system is one of the most essential components within a company. By implementing an information system, a company can ensure the quality of the information produced and make decisions based on that information. PT. Tenma Cikarang Indonesia is a company engaged in the production of plastic injection molds and molding. One of the main weaknesses in the current stock control system at PT. Tenma Cikarang Indonesia is the lack of visibility and accuracy in managing supporting production inventory. Without a computerized system, the company often faces difficulties in tracking available stock, updating depleted items, and anticipating customer demand. In response to these issues, a supporting production inventory control information system was designed to assist the warehouse department in managing item data. This system is web-based and was developed using the waterfall method, with PHP as the programming language and MySQL as the database. Testing was conducted using the User Acceptance Testing (UAT) method. The resulting system is capable of providing information on item data, goods receipt, goods issuance, and generating transaction reports that are useful for users.